Rates and Pathways of N2 Production in a Persistently Anoxic Fjord: Saanich Inlet, British Columbia - Michiels, Céline C.; Huggins, Julia A.; Giesbrecht, Karina E.; Spence, Jenifer S.; Simister, Rachel L.; Varela, Diana E.; Hallam, Steven J.; Crowe, Sean A. (Frontiers in Marine Science, 2019)
Marine oxygen minimum zones (OMZs) support 30-50% of global fixed-nitrogen (N) loss but comprise only 7% of total ocean volume. This N-loss is driven by canonical denitrification and anaerobic ammonium oxidation (anammox), and the distribution and activity of these two processes vary greatly in space and time. Factors that regulate N-loss processes are complex, including organic matter availability, oxygen concentrations, and NO2- and NH4+ concentrations. While both denitrification and anammox produce N2, the overall geochemical outcome of these processes are different, as incomplete denitrification, for example, produces N2O, which is a potent greenhouse gas. Rates of anammox and denitrification and more detailed ecophysiological knowledge of the microorganisms catalyzing these processes are needed to develop more robust models of N-loss in OMZs. To this end, we conducted monthly incubations with 15N-labeled N during anoxic conditions and deep-water renewal cycle in Saanich Inlet, British Columbia, a persistently anoxic fjord. Both denitrification and anammox operated throughout the low oxygen water column with depth integrated rates of anammox and denitrification ranging from 0.150.03 to 3.40.3 and 0.020.006 to 142 mmol N2 m-2 d-1, respectively. Most N2 production in Saanich Inlet was driven by denitrification, with high rates developing in response to enhanced substrate supply from deep water renewal. Dynamics in rates of denitrification were linked to shifts in microbial community composition. Notably, periods of intense denitrification were accompanied by blooms in an Arcobacter population against a background community dominated by SUP05 and Marinimicrobia. Rates of N2 production through denitrification and anammox, and their dynamics, were then explored through flux-balance modeling with higher rates of denitrification linked to the physiology of substrate uptake. Overall, both denitrification and anammox operated throughout the year, contributing to an annual N-loss of 2 x 10-3 Tg N2 yr-1, 37% of which we attribute to anammox and 63% to complete denitrification. Extrapolating these rates from Saanich Inlet to all similar coastal inlets in BC (2478 km2), we estimate that these inlets contribute 0.1 % to global pelagic N-loss.